AB0155 Periostin Deficiency Aggravates Inflammation and Joint Destruction in an Animal Model of Rheumatoid Arthritis. (10th June 2014) - Suh, Y.S.; Kim, H.-O.; Lee, I.-I.; Lim, H.S.; Cheon, Y.-H.; Yoo, W.-H.; Lee, W.-S.; Kim, J.-M.; Kim, S.-H.
Abstract : Background: Periostin is a matricellular protein that expressed in bone, periodontal ligament, heart valve, tendon and skin. Previous study indicated that periostinis linked with several inflammatory diseases such as airway hypersensitivity, periodontal inflammation, and pulmonary fibrosis. However, there is no study to investigate the role of periostin in rheumatoid arthritis (RA). Objectives: This study was performed to assess the function of periostin in K/BxN serum transfer arthritic mice. Methods: Synovial tissues, serum, joint fluid, and fibroblast-like synoviocyte (FLS) were obtained from patients with RA and osteoarthritis (OA). The expression of periostin in synovial tissues was assessed by immunohistochemistry. The levels of periostin were checked by Western blot and enzyme-linked immunosorbent assay (ELISA). K/BxN serum transfer arthritis was induced in periostin knockout (KO) and age-matched wild type (WT) mice. Arthritis severity was assessed by clinical and histopathologic scoring. The levels of inflammatory cytokines in ankles and serum were measured by quantitative PCR and ELISA. The osteoclastogenesis was assessed by using bone marrow monocytes (BMM) from periostin KO or WT mice. Results: Periostin was highly expressed in the synovium of RA patient than OA. The periostin levels were increased in the presence of IL-1β and TNF-α in RA-FLS. The periostin KO mice showed more severe arthritis from day 4 to day 10. The peak clinical scores were: 5.0±0.6 in WT, 7.36±0.5 in periostin KO mice; p<0.01). The periostin KO mice showed aggravated histopathologic findings than WT, respectively: synovial inflammation (3.5±0.6 vs 2.2±0.4; p<0.05), bone erosion (3.8±0.6 vs 1.9±0.5; p<0.05) and cartilage damage (3.2±0.7 vs 1.8±0.5; p<0.05). The level of IL-1b was increased in the serum of periostin KO mice than WT (18 pg/ml ±7.0 vs 5 pg/ml ±1.2; p<0.01). BMMs from periostin KO mice had more TRAP-positive multinucleated cells than WT. Conclusions: This study suggests that regulation of periostin contributes to pathogenesis of RA and periostin has a potential protective role in RA. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4201